2018
DOI: 10.2478/aoas-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Detection of single nucleotide polymorphisms at major prolificacy genes in the Mehraban sheep and association with litter size

Abstract: the present study aimed to investigate the presence of polymorphisms at four known genes controlling ovine prolificacy i.e. BMP15, GDF9, BMPR1B and B4GALNT2 in a sample of 115 iranian Mehraban ewes and their association with litter size (LS) and lambs' birth weight (BW) traits. Using Sanger sequencing of exons and polymorphism specific genotyping, ten SNPs (Single Nucleotide polymorphisms) were observed in only two genes, GDF9 and BMPR1B. Seven SNPs were found in the GDF9 gene on the chromosome 5. Among them, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Additionally, we also sequenced the exon 7 of BMPR1B to genotype for the Booroola mutation ( FecB B , OAR6:29382188A>G, NC_019463.1; Mulsant et al, ). The FecB B prolific allele was absent, but we have observed the recently evidenced SNP (OAR6:29382337G>A) shown to be associated with prolificacy in the Iranian Mehraban breed (Talebi et al, ). As shown in the Table , even if A/A ewes exhibited a lower mean LS (1.68 ± 0.49, n = 6) than G/A (1.97 ± 0.45, n = 5) or G/G ewes (2.22 ± 0.19, n = 3), no significant association was evidenced with the prolificacy of these D'man ++ ewes.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Additionally, we also sequenced the exon 7 of BMPR1B to genotype for the Booroola mutation ( FecB B , OAR6:29382188A>G, NC_019463.1; Mulsant et al, ). The FecB B prolific allele was absent, but we have observed the recently evidenced SNP (OAR6:29382337G>A) shown to be associated with prolificacy in the Iranian Mehraban breed (Talebi et al, ). As shown in the Table , even if A/A ewes exhibited a lower mean LS (1.68 ± 0.49, n = 6) than G/A (1.97 ± 0.45, n = 5) or G/G ewes (2.22 ± 0.19, n = 3), no significant association was evidenced with the prolificacy of these D'man ++ ewes.…”
Section: Resultsmentioning
confidence: 57%
“…Additionally, we also sequenced the exon 7 of BMPR1B to genotype for the Booroola mutation (FecB B , OAR6:29382188A>G, NC_019463.1; Mulsant et al, 2001). The FecB B prolific allele was absent, but we have observed the recently evidenced SNP (OAR6:29382337G>A) shown to be associated with prolificacy in the Iranian Mehraban breed (Talebi et al, 2018). As shown in the breeds (those with improved traits) were first selected in south-west Asia and then spread into Europe, Africa and the rest of Asia (Chessa et al, 2009).…”
Section: Re Sultsmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been suggested that the members of transforming growth factor-β (TGF-β) superfamily, including BMPR-1B, BMP15, and GDF9, affected the ovulation and LS (Demars et al, 2013). Also, numerous studies had explored the polymorphisms of these genes in sheep and goat breeds (Ahlawat et al, 2016;Talebi et al, 2018). Here, we identified large amounts of SNPs in Jining Gray goat, and more than half were novel sites, all the abundant variants extended genetic resource in goat for fecundity traits associated research.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, more attentions have been attracted in reproductive trait study of sheep, four major prolificacy (that is LS) genes have been identified, that are bone morphogenetic protein receptor 1B (BMPR1B, FecB), bone morphogenetic protein 15 (BMP15, FecX), growth differentiation factor 9 (GDF9, FecG), and beta-1,4-N-acetyl-galactosaminyl transferase 2 (B4GALNT2, Fec L ) (Polley et al, 2010;Drouilhet et al, 2013;Våge et al, 2013;Abdoli et al, 2016). In particular, it has been proved an extra ovulation increased per estrus for one copy of BMP15 (0.4) and BMPR-1B (1.5) mutation (Davis, 2005;Abdoli et al, 2016;Talebi et al, 2018). Actually, the mutations of GDF9 and BMP15 genes had been verified to be strongly associated with LS trait in sheep (Demars et al, 2013;Våge et al, 2013).…”
Section: Introductionmentioning
confidence: 99%